Nations: Formation and Interest Dynamics - A E Kafirin (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2012)
The article gives a brief description of historic conditions leading to the formation of nations, and on the basis of attributive features of a nation the set of national interests is identified. Considering national interests as a variable, the author stresses that they depend both on the wishes of ordinary people and on the ability of the state to streamline them in a constructive manner. National interests are classified according to their dynamic characteristics, and the special role of the state as the mouthpiece of national interests is pointed out.